Entrepreneurial experience and the innovativeness of serial entrepreneurs (2018)
Purpose The purpose of this paper is to examine the effects of past entrepreneurial experience on the reported innovativeness of serial entrepreneurs’ subsequent ventures. Design/methodology/approach Building on insights from the generative entrepreneurial learning process and from cognition theories, the authors propose that regardless of the type of entrepreneurial experience, positive or negative, such experience enriches the cognitive schemas of serial entrepreneurs leading them to greater reported innovativeness. The proposed hypotheses are tested on a unique sample drawn from a Catalan adult population survey. Findings Results reveal that practical experience is an essential prerequisite for entrepreneurial learning, and even negative entrepreneurial experience may induce generative entrepreneurial learning suitable for subsequent outperforming ventures for the psychologically strong who have managed to learn from their experience. Practical implications The importance of this study stretches beyond a purely academic discussion and has implications for policy making within the area of business and economic development. Appropriate policy depends on the likeliness for serial entrepreneurs to improve. Thus, if serial entrepreneurs learn from their venturing experiences and/or acquire valuable knowledge from them, they may perform better, on average, in subsequent ventures. If subsequent ventures do build upon prior entrepreneurial experiences, calls for policy to encourage re-entries by entrepreneurs may be warranted, even if those entrepreneurs performed poorly in their previous ventures. Originality/value The authors analyze the impact of past performance of serial entrepreneurs on the reported innovativeness of their subsequence ventures. The contributions of this study stand as: the inclusion of the re-entry decision together with the innovativeness decision of entrepreneurs within the same model; separation of the positive or negative nature of serial entrepreneurs’ past experiences; focus on the entrepreneur rather than the firm as a unit of analysis; the use of a unique primary data set specifically collected for the purpose of this study about the past entrepreneurial experience of the Catalan adult population.